2013
DOI: 10.11607/jomi.2727
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Implant/Abutment System on Torque Maintenance of Retention Screws and Vertical Misfit of Implant-Supported Crowns Before and After Mechanical Cycling

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
21

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 37 publications
5
48
1
21
Order By: Relevance
“…The SEM images showed no significant differences between the three groups, what concurs with the results of a SEM study where no difference was observed between RP and PS groups, in relation to the screw deformation (13). Seemingly, the loss of torque values in this study was not harmful to the implant/abutment junction, but there is no minimum value of torque loss for appropriate implant-supported prostheses performance (21).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The SEM images showed no significant differences between the three groups, what concurs with the results of a SEM study where no difference was observed between RP and PS groups, in relation to the screw deformation (13). Seemingly, the loss of torque values in this study was not harmful to the implant/abutment junction, but there is no minimum value of torque loss for appropriate implant-supported prostheses performance (21).…”
Section: Discussionsupporting
confidence: 88%
“…Some studies evaluated the reverse torque and loosening of abutment retaining screw, (16,(18)(19)(20)(21), but none of these studies evaluated the loosening and reverse torque in platform switching connections and external hexagon implants. The results of the current study corroborate the findings in literature regarding reverse torque values found in implant/abutment connections with external hexagon after mechanical cycling test, as found by Cibirka et al (18), for RP and WP groups.…”
Section: Discussionmentioning
confidence: 99%
“…This was to take the so-called "settling effect" into account. Jorge et al 16) reported that when an unused abutment screw is tightened, the metals settle together over the space of a few minutes. Therefore, in our study, the implant system was left for 5 min after tightening.…”
Section: Experimental Apparatus and Methodsmentioning
confidence: 99%
“…There have been clinical studies 2,3) , as well as numerous basic research studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] on abutment screw looseness, and reasons for looseness that have been put forward include insufficient fastening torque of the screw, unfitted components, inappropriate direction or position of implant placement, and poor occlusal status [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Looseness of the abutment screw causes poor fit of the superstructure, and can lead to fracture of the abutment screw and superstructure damage or detachment, as well as fracture of the implant or resorption of the periimplant bone.…”
Section: Introductionmentioning
confidence: 99%
“…The crowns were torqued to the implants (32 N.cm), according to manufacturer's recommendation, using a hexagonal wrench. After 3 min, the screw was retightened to the same torque to minimize embedment relaxation 23 . The placement torque was measured by the digital torquemeter with a 0.1 precision.…”
Section: Methodsmentioning
confidence: 99%